Determinasi Konsep Diri dan Ketahanmalangan (Adversity Quotient) terhadap Kreativitas Mahasiswa Jurusan S1 Pendidikan Matematika IKIP PGRI Bali: Determination of Self-Concept and Adversity Quotient on Student Creativity in S1 Mathematics Education Department IKIP PGRI Bali - I Dewa Putu Juwana; Dewa Gede E. Sastra Wiguna (Emasains : Jurnal Edukasi Matematika dan Sains, 2019)
This study aims to determine: (1) determinate on the self concept of creativity undergraduate students education of mathematic Departement, (2) determinate on the adversity quotientof creativity undergraduate student seducation of mathematic Departement, and (3) determinate on the self conceptand adversity quotientof creativity undergraduate students education of mathematic Departement. This study is a correlational study. The research was conducted at undergraduate degree education of mathematic Departement IKIP PGRI Bali. The sample in this study as many as 75 people, sampling is done using strata random sampling technique. Methods of data collection in the form of tests andquestionnaires using a Likert scale. Methods of data analysis used was multiple regression. The results showed that (1) the self concept contribute of creativity undergraduate students education of mathematic Departement(r =0.77, p <0.05 andt=16,11, p <0.05), (2) the adversity quotientcontributes of creativity undergraduate students education of mathematic Departement(r =0.60, p <0.05 andt=8.00, p <0.05)), (3) the self conceptand adversity quotient contributes of creativity undergraduate students education of mathematic Departement(r =0.76, p <0.05 andF=48,49, p <0.05) as well as having effective contribution by 58% .